CUTANEOUS larvae Migrans - Palgunadi, Bagus Uda (Universitas Wijaya Kusuma Surabaya, 2010)
Cutaneous Larva Migrans or Creeping eruption is a skin lesion in humans caused by infection with larvae of animal hookworms Ancylostoma caninum and Ancylostoma especially braziliense. Transmission occurs through the skin and will occur in the epidermal groove winding erythematous - serpentine. Although thissyndrome can be cured by itself but the itching and the risk of secondary infection is very high. Thiabendazole is an anthelmintic options to combat the transmitting worm larvae.Â